2018
DOI: 10.1038/s41598-018-22109-y
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of growth plate vascularization during coupling with osteogenesis in tibial dyschondroplasia of chickens

Abstract: Tibial dyschondroplasia (TD) is the most-prevalent leg disorder in fast-growing chickens; it is intractable and characterized by abnormal endochondral bone formation of proximal tibial growth-plates (TGPs). Previous studies have shown that bone is a highly vascularized tissue dependent on the coordinated coupling between angiogenesis and osteogenesis, but the underlying mechanisms of bone formation and bone remodeling are poorly defined in TD chickens. Here, we observed that inhibition of vasculogenesis and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
(98 reference statements)
2
32
0
Order By: Relevance
“…KEGG pathways results of our study demonstrated that calcium signaling pathway was not enriched and differentially expressed on day 6, which was the clear indication of decreased or less Ca + ions transportation compared on day 2 and 15. The results of this study supported and added in the findings of Huang et al, [20], thiram significantly downregulated the expression of ATP2A3, which could be responsible for the reduction of Ca + 2 ions transportation similarly in TD chickens. Moreover, calcium signaling pathway shows that the chickens are being recovered from the deleterious effect of thiram on day 15.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…KEGG pathways results of our study demonstrated that calcium signaling pathway was not enriched and differentially expressed on day 6, which was the clear indication of decreased or less Ca + ions transportation compared on day 2 and 15. The results of this study supported and added in the findings of Huang et al, [20], thiram significantly downregulated the expression of ATP2A3, which could be responsible for the reduction of Ca + 2 ions transportation similarly in TD chickens. Moreover, calcium signaling pathway shows that the chickens are being recovered from the deleterious effect of thiram on day 15.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, ATP2A3 was upregulated on day 2 and downregulated on day 15, which have been evaluated previously as a transporter of Ca + 2 ions [19]. A recent study reported that Ca + 2 ions decreased in TD chickens [20]. KEGG pathways results of our study demonstrated that calcium signaling pathway was not enriched and differentially expressed on day 6, which was the clear indication of decreased or less Ca + ions transportation compared on day 2 and 15.…”
Section: Discussionmentioning
confidence: 45%
“…Bone growth depends also on the action of chondrocytes from the growth plate cartilage [44]. Recently, is has been shown that the growth plate cartilage of birds with induced dyschondroplasia is characterized by increased hypertrophic zone, and inhibited bone mass-related and bone structure-related parameters [45]. Chickens form the CPS group had heavier, longer and wider tibiotarsus than those of SBM group, with reduced hypertrophic zone and increased ossification zone and total growth plate thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin-eosin (HE) staining was performed to observe the degree of lesion changes. The area of lipid droplets in the liver and femoral head were analyzed using ImageJ ( Huang et al, 2018 ; Jahejo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The bird had an obvious gait defect, which affected its ability to move about; Gait score of 4 (E) The bird had a severe gait defect; Gait score of 5 (F) The bird was incapable of sustained walking on its feet. the liver and femoral head were analyzed using ImageJ (Huang et al, 2018;Jahejo et al, 2020).…”
Section: Target Genementioning
confidence: 99%